Fiscal Stability and Macroeconomic Environment in Nigeria: A Further Assessment - Bashir Olayinka Kolawole (Theory, Methodology, Practice, 2021)
This paper examines the relationship between fiscal stability and macroeconomic environment in Nigeria using time series data covering the period 1981-2019. As Nigeria’s debt appears excessive amid macroeconomic imbalance, different concerns are raised about the capacity of the government to repay the debt. In this regard, several studies are conducted on the sustainability of the country’s debt. But then, as a long-run analysis, assessment of debt sustainability is prone to considerable uncertainty and large margins of error. Thus, the relevance and need for a short-run analysis which serves as the basis for assessing fiscal stability. In the process, while multiple structural breaks are revealed in the total revenue, exchange rate, and total debt series, a feedback causal-effect is affirmed between fiscal stability and interest rate. Consequently, the short-run analysis establishes negative impacts from each of debt and exchange rate, as against positive effect from revenue on fiscal stability. As such, given a mixed relationship between fiscal stability and certain macroeconomic factors, an improved revenue collection is suggested with reduction in borrowing.